Quantifying the impact of known clinical risk factors and deprivation on preterm births: a retrospective cohort study. (7th June 2011) - Agarwal, U; Taylor-Robinson, D; Yoxall, B; Platt, M J; Alfirevic, Z
Abstract : Objective: To explore preterm birth (PTB) rates according to the clinical risk status with a particular focus on low risk pregnancies and their socioeconomic status. Design: Retrospective cohort study. Population: 51 426 live births from women booked at the Liverpool Women's Hospital between 2002 and 2008. Main outcome measure: The primary outcome was PTB before 34+0 gestational weeks. Pregnancies were stratified into four mutually exclusive cohorts: uncomplicated singleton pregnancies, pregnancies with medical disorders, previous history of PTB and multiple pregnancies. For women in low and high risk group, multiple logistic regression and generalised additive models were used to explore the effect of Index of Multiple Deprivation, smoking status, BMI, parity and ethnicity. Results: Overall, PTB rate was 2.7%, ranging from 1.3% in the low risk group, 6.3% with medical disorders, 8.7% with previous PTB and 21.4% in multiple pregnancies. In the low risk group, there was a significant difference in PTB rates between the most and least deprived quintile (OR 1.5, 95% CI 1.2 to 1.9). Being underweight and smoking were both independently associated with a significantly increased risk of preterm birth. Conclusion: It is possible to identify pregnant women at a significantly higher risk of PTB using routinely collected data. Deprivation has significant impact on PTB rates in low risk women, but not in women with known obstetric risk factors. In low risk women, the relationship between low socio-economic status and PTB appears to be mediated by low maternal weight and smoking.